2022
DOI: 10.25122/jml-2021-0380
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of telogen effluvium hair loss in COVID-19 patients and its relationship with disease severity

Abstract: COVID-19 is a concerning global pandemic. Common manifestations are fever and respiratory symptoms. In addition, recent studies reported dermatological manifestations as extrapulmonary signs. One of these is telogen effluvium which is related to post COVID-19 comorbidities. The aim of this study was to assess the prevalence of telogen effluvium among COVID-19 patients. This observational cross-sectional study included 198 patients who were admitted for COVID-19. The PCR test was performed to detect positive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
1
7
0
2
Order By: Relevance
“…However, both younger (mean age 31 years) and older age groups (49 years) have been affected, which could possibly be due to geographical variation in the prevalence of COVID-19 infection [5,13,14]. There was a female preponderance in the present study, as seen in other studies as well, possible explanations being, longer hair length and higher vulnerability of female hair follicles due to role of estrogen and progesterone hormones in the pathophysiology of hair loss [1,2,5,11,[14][15][16][17]. Higher prevalence of anemia (20%) and low ferritin levels (30%) in our patients who were predominantly females, can also be a contributing factor; as was also observed by Babaei et al who reported the presence of iron de ciency anemia in 13.8% of their patients [14].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…However, both younger (mean age 31 years) and older age groups (49 years) have been affected, which could possibly be due to geographical variation in the prevalence of COVID-19 infection [5,13,14]. There was a female preponderance in the present study, as seen in other studies as well, possible explanations being, longer hair length and higher vulnerability of female hair follicles due to role of estrogen and progesterone hormones in the pathophysiology of hair loss [1,2,5,11,[14][15][16][17]. Higher prevalence of anemia (20%) and low ferritin levels (30%) in our patients who were predominantly females, can also be a contributing factor; as was also observed by Babaei et al who reported the presence of iron de ciency anemia in 13.8% of their patients [14].…”
Section: Discussionmentioning
confidence: 52%
“…They also found an association of trichodynia with dysgeusia and anosmia, postulating an underlying neurogenic pathogenesis for all [25]. Trichodynia corresponds to a complex symptom comprising scalp pain, pruritus or burning sensation on touching or combing through the scalp, which may be a sign of severity or a warning symptom of imminent hair shedding before hair loss begins [17,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabela com todos os artigos selecionados após todos os critérios de seleção Umakantahan, et al, 2020;Silva, 2021;Bem, et al, 2021;Khaled, et al, 2020;Wu, 2019;Bueno, et al, 2022;Abrantes, et al, 2021;Andrade, et al, 2017;Mieczkowska, et al, 2021;Oliveira, 2021;Gomes, 2021;Zhang, et al, 2021;Rizzetto, et al, 2020;Seyfi, et al, 2022;Hussain, et al, 2021;Queiroz, 2022;Cruz, et al, 2022;Benedito, et al, 2022;Sociedade brasileira de dermatologia, 2021;Pereira, et al, 2021;Soncino, et al, 2017;Colaço, et al, 2017;Carvalho, 2018;Gobira, et al, 2020Fonte: Autores (2022.…”
Section: Metodologiaunclassified
“…Os pacientes com SARS-CoV-2 revelaram níveis mais elevados de citocinas pró-inflamatórias (fator de necrose tumoral, interleucina 1b, interleucina 6 e interferon tipos 1 e 2), o que pode explicar as manifestações cutâneas associadas à infecção, como vasculopatia livedoide, urticária, dedos COVID-19, e uma erupção cutânea semelhante à catapora. (Seyfi, et al, 2022) Em um estudo realizado por Nabeel Hussain, da Escola de Medicina da Universidade Saba, The Bottom, Holanda, foi observado que a TE aguda ocorreu em torno de uma duração média de 74 dias após o início dos sintomas de COVID-19. Isso é mais precoce do que a TE aguda clássica, que ocorre aproximadamente 3 a 4 meses após um evento desencadeante.…”
Section: Eflúvio Telógeno Em Pacientes Acometidos Pela Covid-19unclassified